Le régiment de cavalerie de la Garde républicaine - Chef d’escadron Frédéric Daugérias (In Situ)
The cavalry regiment of the French Garde républicaine. This French cavalry regiment of the Garde républicaine is under the command of the national gendarmerie. It has about 500 horsemen and women and 460 horses. It is a unit that has a long history, stretching back over the centuries with the same tasks of honouring officials of the French State and the guests to France and carrying out various security missions. These of course have evolved considerably over the years and are now adapted to the security risks of the twenty-first century. However, in this cavalry regiment, rusticity and discipline remain the key words in the training both of the men and of the horses.